Application of Calculation of Ranking Funding Officer at the Bank(Aplikasi Perhitungan Rangking Funding Officer Pada Bank) - Deval Gusrion (Jurnal KomtekInfo, 2020)
Bank is a business entity that collects funds from the public in the form of deposits and distributes them to the public in the form of credit and or other forms. To raise funds, bank officers are known as funding officers who have the main task of collecting funds in the form of savings, current accounts and deposits. Generally banks already have monitoring tools, dashboards and reports on the achievement of funds, but these tools do not yet present a ranking for funding officers. One of the things needed to support the improvement of funding officer performance is the making of individual ranking, for that purpose an application for ranking calculation is made using the PHP programming language whose data is sourced from existing monitoring tools, it is hoped that this application can help the relevant part to accelerate presentation of individual ranking of funding officers.